Local and Systemic CD4+ T Cell Exhaustion Reverses with Clinical Resolution of Pulmonary Sarcoidosis - Charlene Hawkins; Guzel Shaginurova; D. Auriel Shelton; Jose D. Herazo-Maya; Kyra A. Oswald-Richter; Joseph E. Rotsinger; Anjuli Young; Lindsay J. Celada; Naftali Kaminski; Carla Sevin; Wonder P. Drake (Journal of Immunology Research)
Investigation of the Th1 immune response in sarcoidosis CD4+ T cells has revealed reduced proliferative capacity and cytokine expression upon TCR stimulation. In other disease models, such cellular dysfunction has been associated with a step-wise, progressive loss of T cell function that results from chronic antigenic stimulation. T cell exhaustion is defined by decreased cytokine production upon TCR activation, decreased proliferation, increased expression of inhibitory cell surface receptors, and increased susceptibility to apoptosis. We characterized sarcoidosis CD4+ T cell immune function in systemic and local environments among subjects undergoing disease progression compared to those experiencing disease resolution. Spontaneous and TCR-stimulated Th1 cytokine expression and proliferation assays were performed in 53 sarcoidosis subjects and 30 healthy controls. PD-1 expression and apoptosis were assessed by flow cytometry. Compared to healthy controls, sarcoidosis CD4+ T cells demonstrated reductions in Th1 cytokine expression, proliferative capacity (p<0.05), enhanced apoptosis (p<0.01), and increased PD-1 expression (p<0.001). BAL-derived CD4+ T cells also demonstrated multiple facets of T cell exhaustion (p<0.05). Reversal of CD4+ T cell exhaustion was observed in subjects undergoing spontaneous resolution (p<0.05). Sarcoidosis CD4+ T cells exhibit loss of cellular function during progressive disease that follows the archetype of T cell exhaustion.